Desain Dan Analisis Mesin Pencuci Cacahan Botol Plastik Untuk Industri Kecil Dengan Menggunakan Simulasi - Permadi, Nafakah Arif; , Joko Sedyono, Ph.D; , Masyrukan, ST, MT (2016)
The purpose of this study was to create a design, analysis, and simulation of the propeller shaft and the washing machine shredded small plastic bottle with Solidworks 2010 for industri. It was also to determine the value of the yield strength and the value of the von mises maxima forward from the material used on the shaft and propeller so we get the Safety Factor to determine the safety of the materials used. In the process of design, analysis, and simulation of the investigated on the shaft and propeller on a plastic bottle washer machine. The material used on the shaft is steel S 35 C - D, while the material used in the blades are aluminum 2014 alloy. Software used in the present study using Solidworks 2010. The results of the analysis and simulation of the shaft and blades on the washing machine plastic bottles shows that the value of the yield strength of the shaft is (282.685.056 N / mm²), while the value of maximum von mises of the material used on the shaft is 149.080.416 N / mm², Safety Factor shaft is 3. Fom material used on the shaft declared safe. In addition the value of the yield strength of the propeller is (96.509.800 N/ mm²), while the value of maximum von mises of the material used on the propeller is 6.241.970 N/mm², Safety Factor 1. From the baling is the material used the baling declared safe.